STRATEGI SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN TEMPAT HIBURAN UMUM KARAOKE KOTA PEKANBARU - Denis Juan Lim; Adianto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2023)
Pekanbaru City has grown rapidly and become the center of Riau Province. Rapid population growth has had an impact on the economy and social but has led to social problems such as Commercial Sex Workers (CSWs) who roam a lot in karaoke public entertainment venues. This research aims to analyze the Strategy and identify the Strategy implemented by the Pamong Praja Police Unit. This research uses Mintzberg's theory in Asaretkha Adjane Annisawati (2022) which uses indicators: Plan, Ploy, Pattern, Position, Perspective. This research uses descriptive qualitative research. The results of this study found that the strategy implemented was still less effective because of the lack of innovation and lack of assertiveness in policing, there were still many violations of regulations in entertainment venues. Therefore, there is a need for adjustments to the strategy of the Pekanbaru Pamong Praja Police Unit that is more adaptive, stricter law enforcement, and continuous updates to overcome this growing problem.